On the design of linear precoders for orthogonal space-time block codes with limited feedback - Sanayei, S.; Love, D.J.; Nosratinia, A. (IEEE Wireless Communications and Networking Conference, 2005, 2005)
Orthogonal space-time block codes (OSTBC) are among the most practical space-time codes due to their simplicity and optimal decoding. When information about the channel is available at the transmitter, the performance of OSTBC can be significantly improved by exploiting the array gain. However, providing full knowledge of channel state at the transmitter may not he affordable in many practical cases. Thus exploiting partial channel knowledge to improve the performance of OSTBC seems to be attractive. In this work we investigate the design of linear precoders with partial channel knowledge at the transmitter combined with an orthogonal space time code. We derive the condition for optimal precoder subject to a power constraint on the whole transmission block. We also propose a technique for precoder codebook design with limited feedback.